Metod Da'wah Wali Songo - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1998)
Wali Songo had used the very interesting method in their dakwah, which attracted the people of java to Islam. However, this method had its own weaknesses because it produced the synergetic Muslims in religious practice. The paper discusses the method of dakwah of Wali Songo, why it attracted the people of java and how far it could be applied to the contemporary approach of dakwah in Malaysia